Ultrasound aspects and risk factors associated with urogenital schistosomiasis among primary school children in Mali - IBIKOUNLE, MOUDACHIROU (My University, 2023)
Abstract Background Urogenital schistosomiasis is endemic in Mali and is a major cause of serious morbidity in large parts of the world. This disease is responsible for many socio-economic and public health issues. The aim of this study was to investigate the impact of the disease on morbidity and to describe demographic and socioeconomic factors in relation to the status of children with urogenital schistosomiasis in Mali. Methods We conducted a cross-sectional study in November 2021 of 971 children aged 6 to 14 years selected at random from six schools in three districts in the Kayes Region of Mali. Demographic and socioeconomic data were collected on survey forms. Clinical data were collected following a medical consultation. Hematuria was systematically searched for through the use of strips. The search for Schistosoma haematobium eggs in urine was done via the filtration method. The urinary tract was examined by ultrasound. Associations between each of these variables and disease infection were tested using multivariate logistic regression. Results The overall prevalence of urinary schistosomiasis detected was 50.2%. The average intensity of infection was 36 eggs/10 ml of urine. The associated risk factors for urogenital schistosomiasis showed that children who bathed, used the river/pond as a domestic water source, and who habitually urinated in the river/pond were more affected (P < 0.05). Children with farming parents were most affected (P = 0.032). The collection of clinical signs revealed that boys had more pollakiuria (58.6%) and dysuria (46.4%) than girls. Ultrasound data showed that focal lesion rates were recorded in all villages with the lowest rate in Diakalel (56.1%). Ultrasound and parasitological findings showed that irregularity and thickening were strongly associated with urinary schistosomiasis (P < 0.0001). Conclusions Schistosoma haematobium infection was still endemic in the study site despite more than a decade of mass treatment with praziquantel. However, the high percentage of symptoms associated with high intensity rein forces the idea that further studies in terms of schistosomiasis-related morbidity are still needed.
Keywords: Schistosoma haematobium; Morbidity; Prevalence; Risk factor; Mali